Universiti Utara Malaysia aims to be among top 300 by 2020 - The Sunday Post, (Kuching) (The Sunday Post (Kuching), 2017)
KUALA LUMPUR: Universiti Utara Malaysia (UUM) in Sintok. Kedah, aims to be among the world's top 300 universities in the Quacquarelli Symonds (QS) World University Rankings (WUR) by 2020, in line with UUM's Phase 2 of its Strategic Plan (20162020).